Genome‐wide investigation and comparative analysis of MATE gene family in Rosaceae species and their regulatory role in abiotic stress responses in Chinese pear (Pyrus bretschneideri). Issue 3 (29th August 2021) - Manzoor, Muhammad Aamir; Li, Guohui; Abdullah, Muhammad; Han, Wang; Wenlong, Han; Yang, Zhang; Xinya, Wang; Yu, Zhao; Xiaofeng, Feng; Qing, Jin; Shafique, Muhammad Sohaib; Cai, Yongping
Abstract: The Multidrug and Toxic Compound Extrusion (MATE) protein belongs to a secondary transporter gene family, which plays a primary role in transporting many kinds of substrates such as organic compounds, secondary metabolites, and phytohormones. MATE protein members exist in both prokaryotes and eukaryotes. However, evolution and comprehensive analysis of the MATE genes has not been performed in Rosaceae species. In the present study, a total of 404 MATEs genes were identified from six Rosaceae genomes ( Prunus avium, Pyrus bretschneideri, Prunus persica, Fragaria vesca, Prunus mume, and Malus domestica ) and classified into eight main subfamilies (I–VII) based on structural and phylogenetic analysis. Microcollinearity analysis showed that whole‐genome duplication events might play a vital role in the expansion of the MATE genes family. The Ka/Ks analysis, chromosomal localization, subcellular localization, and molecular characteristics (length, weight, and pI) were performed using various bioinformatics tools. Furthermore, different subfamilies have different introns‐exons structures, cis ‐acting elements, and conserved motifs analysis, indicating functional divergence in the MATE family. Subsequently, RNA‐seq analysis and real‐time qRT‐PCR were conducted during Chinese pear fruit development. Moreover, PbMATE genes were significantly expressed under hormonal treatments of MeJA (methyl jasmonate), SA (salicylic acid), and ABA (abscisic acid). Overall, our results provide helpful insights into the functions, expansion complexity, and evolutions of the MATE genes in Chinese pear and five Rosaceae species.